Participatory fecal collection on wild sumatran elephants' dungs in South Sumatra: The significant role of community involvement - Pratiwi, Dian Neli; P. Haryanto, Sugeng; Yanti, Yulianti; Arum, Setiawan; Samsul , Bakri; Winda, Indriyanti; Elly Lestari, Rustiati (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Sumatran elephant Elephas maximus sumatranus is a critically endangered species under pressure of habitat fragmentation and human-elephant conflict (HEC) such as in one plantation and/or settlement area next to its natural habitat, Simpang Tiga Abadi, Selapan, South Sumatera. Due to HEC, local people may experience economic loss and human casualty. Simpang Tiga Abadi is avillage, especially 5 sub-settlements directly close to the production forest area of PT. Bumi Khatulistiwa Mandiri, which is the natural habitat of sumatran elephants. The communities collaborated and company were formed an elephant watch group to monitor and deter sumatran elephants from entering plantation areas and settlements. On the other side, sumatran elephants entering the plantation may give some conservation support as indirect conflict mitigation approaches. A non-invasive sampling can be done by gathering information on its fecal based genetic diversity and may become one of supporting sumatran elephant conservation efforts. Under the Center for Applied Science Studies, Sriwijaya University project: